Students’ Perspectives on Celebrity Endorsement and Purchase Behavior - Shrestha, Dipika; Ranabhat, Namrata; Adhikari, Pramita; Neupane, Bikalpa; Pandey, Kushal; Shrestha, Sneha; Mishra, Sanjib (Darul Yasin Al Sys, 2025)
This study investigates the influence of celebrity endorsements on students’ purchasing decisions at Shankardev Campus. Adopting a deductive approach within a positivist paradigm, the research integrates descriptive and causal designs to examine the impact of celebrity attributes on consumer behavior. Primary data were collected from 115 students through structured questionnaires, capturing perceptions of celebrity appeal, credibility, and brand influence. Statistical techniques, including mean analysis, correlation, and regression, were employed to assess relationships and predict the effects of these attributes on purchase intentions. The results indicate that expertise is the most influential endorsement characteristic in shaping buying behavior, surpassing appeal and credibility. These findings underscore the importance of selecting endorsers with strong perceived knowledge and credibility to enhance marketing effectiveness. The study adds to the literature on celebrity endorsements in emerging markets, with specific relevance to Nepal, and provides actionable insights for advertisers seeking to engage young, socially active consumers.